Pengaruh Akuntansi Lingkungan (Green Accounting), Pertumbuhan Penjualan, dan Ukuran Perusahaan terhadap Profitabilitas: (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Indeks Saham Syariah Indonesia Periode 2018-2022) - Miftahur Rahmah; Sandra Dewi (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
The purpose of establishing a company is to obtain high profitability. However, in practice, there are still many companies that turn a blind eye to managing the environment in order to increase profitability, of the 105 manufacturing companies listed on the Indonesian Sharia Stock Index, less than a quarter of all manufacturing companies implement green accounting. And there are many companies that experience losses even though their sales increase. This study aims to determine the effect of environmental accounting (green accounting), sales growth, and company size on profitability in manufacturing companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2018-2022 period. This study uses a descriptive research type with a quantitative approach. The sampling method uses the purposive sampling method. The data used are secondary data in the form of financial reports and annual reports on manufacturing companies listed on the Indonesian Sharia Stock Index for the 2018-2022 period. The analysis technique used is multiple linear regression analysis processed using the Eviews Version 12 application. The results of this study indicate that the environmental accounting variable (green accounting) has a positive but not significant effect on profitability. The sales growth variable has a positive and significant effect on profitability. The company size variable has a negative but not significant effect on profitability. And the variables of environmental accounting (green accounting), sales growth, and company size have a positive and significant effect on profitability.